MATERIALES RECICLABLES PARA EL DESARROLLO DE LA CREATIVIDAD DE LOS NIÑOS DE EDUCACIÓN INICIAL NIVEL II” - ALVARADO HERNANDEZ GRACE MARIA (2024)
In summary, this research work explores the impact of recyclable materials on the development of creativity of children at the María Luisa de Sotomayor Educational Unit level II. The study is based on the proposition that creativity is a fundamental skill for the cognitive and emotional development of children, and that it can be enhanced through the use of accessible and sustainable resources. The same one that aims to determine the relationship of the use of recyclable materials for the development of creativity of the children of Initial Education II, along with this objective, the methodology will be used where a non-experimental design is chosen due to the observational nature of The research will also apply the mixed approach which will allow capturing the richness and complexity of the experiences of children and teachers, providing a solid basis for future educational mediations and additional knowledge in this field, with relevant techniques such as observation and interview. Just as instruments such as a questionnaire and an observation sheet will also be used. The use of recyclable materials in training actions has proven to be highly effective in stimulating creativity in children. The diversity and flexibility of these materials allow children to explore new ideas, experiment with different shapes and textures, and develop solutions to simple problems. These materials provide an affordable and affordable way to foster creativity, problem-solving, and teamwork skills.